Life great short stories by women - Hislop, Victoria (London Head of Zeus, 2014)
Love is, of course, a central preoccupation of literature...' Victoria Hislop, bestselling author, and champion of the short story, has chosen her favorite short stories by women writers. Here are prizewinners, famous wits, well-known feminists, national treasures and rising stars. Love is represented in this volume in all its guises - romantic, maternal, happy and haunting. CONTRIBUTORS: Katherine Mansfield, Dorothy Parker, Doris Lessing, Margaret Drabble, Angela Carter, Margaret Atwood, Ellen Gilchrist, Alice Walker, Mavis Gallant, Carol Shields, Anne Enright, Elspeth Davie, Alison Lurie, Jennifer Egan, Jeanette Winterson, Claire Boylan, Maggie Gee, Colette Paul, Rachel Seiffert, Yiyun Li, Nadine Gordimer, Miranda July, Chimamanda Ngozi Adichie, Carys Davies, Alison MacLeod, Emma Donoghue, Roshi Fernando, M. J. Hyland and Avril Joy.
First published within The story, Head of Zeus, 2013.
UCWS-3393g donated by Adrienne Maguddayao - October 2018
Keywords: Short stories, English -- Women authors; Women -- Fiction; Women in literature